Winnipeg 1919: The Strikers' Own History of the Winnipeg General Strike - Penner, Norman (Lorimer, 2019)
The most important primary document from the Winnipeg General Strike now back in print with a new introduction on the occasion of the strike's 100th anniversary On May 15, 1919 workers from across Winnipeg, ranging from metal workers to telephone operators, united to spark the largest worker revolt in Canadian history. Even the Winnipeg police voted to join the strike, although they remained on duty at the request of the strike committee in order to prevent martial law. Approximately 30,000 workers walked off the job over the next six weeks, and the city was overtaken by lively demonstrations and marches in what the media, the city's leaders, and the federal government called a "Bolshevik uprising." The clash ended violently when RCMP on horseback charged and shot into a crowd of striking workers resulting in deaths, beatings, and arrests. The strike was called off and workers returned to their jobs without having earned the rights to higher wages and collective bargaining. Following the strike, union leaders published this account of the events leading up to and during the strike. Their volume is the most significant primary source describing the workers' experience of the strike. This book offers the full document in its original format along with an introduction to the 1974 edition by labour historian and activist Norman Penner. His essay has had a major impact on later research. This volume also includes a new introduction by historian Christo Aivalis discussing how the lessons learned in 1919 remain relevant today. Also included in this book are the key documentary photographs of strike events, including a minute-by-minute sequence showing the final RCMP fatal assault on the strikers. --Publisher's description

Divided Province: Ontario Politics in the Age of Neoliberalism - Albo, Gregory; Evans, Bryan M. (McGill-Queens University Press, 2019)
No government jurisdiction in Canada has so radically transformed its public policies over the past decades as Ontario, and yet the province has also maintained a striking degree of political stability in its party system. Since the 1990s, neoliberalism has been the point of reference in constructing policy agendas for all of Ontario's political parties. It has guided the strategy for governance of the dominant Liberal Party since 2003, even as it divides the province between workers and employers, north and south, rural and urban, and racialized minorities and the majority population. With a focus on the governments of Mike Harris, Dalton McGuinty, and Kathleen Wynne, Divided Province brings together leading researchers to dissect the province's public policies since the 1990s. Presenting original, state-of-the-art research, the book demonstrates that, although the Conservative government of Mike Harris implemented the sharpest and most profound shift towards the establishment of a neoliberal regime in the province, the subsequent Liberal governments consolidated that neoliberal turn. The essays in this volume explore the consequences of this ideological turn across a spectrum of policies, including health, education, poverty, energy, employment, manufacturing, and how it has impacted workers, women, First Nations, and other distinct communities. The first book to offer a comprehensive critical account of neoliberalism in Ontario, Divided Province overturns conventional readings of the province's politics and suggests that building a more democratic and egalitarian alternative to the current orthodoxy requires nothing less than a radical rupture from existing policies and political alliances. Without such a decisive break, political space may well open up again for the populist right. --Publisher's description

Everyday Transgressions: Domestic Workers' Transnational Challenge to International Labor Law - Blackett, Adelle (ILR Press, an imprint of Cornell University Press, 2019)
Adelle Blackett tells the story behind the International Labour Organization's (ILO) Decent Work for Domestic Workers Convention No. 189, and its accompanying Recommendation No. 201 which in 2011 created the first comprehensive international standards to extend fundamental protections and rights to the millions of domestic workers laboring in other peoples' homes throughout the world. As the principal legal architect, Blackett is able to take us behind the scenes to show us how Convention No. 189 transgresses the everyday law of the household workplace to embrace domestic workers' human rights claim to be both workers like any other, and workers like no other. In doing so, she discusses the importance of understanding historical forms of invisibility, recognizes the influence of the domestic workers themselves, and weaves in poignant experiences, infusing the discussion of laws and standards with intimate examples and sophisticated analyses. Looking to the future, she ponders how international institutions such as the ILO will address labor market informality alongside national and regional law reform. Regardless of what comes next, Everyday Transgressions establishes that domestic workers' victory is a victory for the ILO and for all those who struggle for an inclusive, transnational vision of labor law, rooted in social justice. --Publisher's description
Keywords: Decent work; Domestic work; Employées de maison Droit Législation; Foreign workers; Foreign workers Legal status, laws, etc; Hausarbeit; Hauswirtschaftsgehilfin; Household employees Legal status, laws, etc; International labour law; Internationales Arbeitsrecht; Labor laws and legislation, International; Legal status; Travail (Droit international) Législation; Travailleurs étrangers Droit Législation; Übereinkommen über menschenwürdige Arbeit für Hausangestellte 2011 Juni 16

A Diminished Roar: Winnipeg in the 1920s - Blanchard, Jim (University of Manitoba Press, 2019)
The third instalment in Jim Blanchard's popular history of early Winnipeg, 'A Diminished Roar' presents a city in the midst of enormous change. Once the fastest growing city in Canada, by 1920 Winnipeg was losing its dominant position in western Canada. As the decade began, Winnipeggers were reeling from the chaos of the Great War and the influenza pandemic. But it was the divisions exposed by the 1919 Winnipeg General Strike which left the deepest marks. As Winnipeg wrestled with its changing fortunes, its citizens looked for new ways to imagine the city's future and identity. Beginning with the opening of the magnificent new provincial legislature building in 1920, A Diminished Roar guides readers through this decade of political and social turmoil. At City Hall, two very different politicians dominated the scene. Winnipeg's first Labour mayor, S.J. Farmer, pushed for more public services. His rival, Ralph Webb, would act as the city's chief 'booster' as mayor, encouraging U.S. tourists with the promise of 'snowballs and highballs.' Meanwhile, promoters tried to rekindle the city's spirits with plans for new public projects, such as a grand boulevard through the middle of the city, a new amusement park, and the start of professional horse racing. In the midst of the Jazz Age, Winnipeg's teenagers grappled with 'problems of the heart, ' and social groups like the Gyro Club organized masked balls for the city's elite. --Publisher's description
Keywords: 1900-1999; Années vingt (Vingtième siècle); Electronic books; HISTORY / Canada / Post-Confederation (1867-); History; Manitoba Winnipeg; Nineteen twenties; Winnipeg (Man.) History 20th century

Land of Triumph and Tragedy: Voices of the Italian Fallen Workers: A Century of Italian Immigration to Canada: Immigrants Who Made It and Those Who Perished Trying - Breda, Paola; Toppan, Marino (Verità, 2019)
The Embassy of Italy, the Consulate General of Italy in Toronto and Villa Charities join together with authors Paola Breda and Marino Toppan to present a ground-breaking new history of the Italian-Canadian immigration experience, finally including the previously untold story of the thousands of Italian Fallen Workers who died building this beautiful country — a story that’s destined to become a new piece of Canadian History. Compiled after decades of research by Toppan, this epic new volume includes countless contributions from across the country, from scholars of Italian-Canadian history and the families of the fallen themselves. This ground breaking new book includes profiles of those in the Italian community in Canada who triumphed with incredible successes, those who died in tragic circumstances, as well as in-depth studies on immigration patterns, labour history, socio-adaptive patterns, labour action, strife and hardships experienced, and many more themes in the Italian-Canadian identity. It even coins a new phrase: Canadianità! --Publicity release, May 23, 2019

1919 : une histoire graphique de la grève générale de Winnipeg - Collectif d'histoire graphique; Lester, David; Michaud, William; Graphic History Collective (Between the Lines, 2019)

Clearing the Plains: Disease, Politics of Starvation, and the Loss of Aboriginal Life - Daschuk, James W. (Canadian plains studies, 2019)
Revealing how Canada's first Prime Minister used a policy of starvation against Indigenous people to clear the way for settlement, the multiple award-winning Clearing the Plains sparked widespread debate about genocide in Canada. In arresting, but harrowing, prose, James Daschuk examines the roles that Old World diseases, climate, and, most disturbingly, Canadian politics—the politics of ethnocide—played in the deaths and subjugation of thousands of Indigenous people in the realization of Sir John A. Macdonald’s "National Dream. " It was a dream that came at great expense: the present disparity in health and economic well-being between Indigenous and non-Indigenous populations, and the lingering racism and misunderstanding that permeates the national consciousness to this day. This new edition of Clearing the Plains has a foreword by Pulitzer Prize winning author, Elizabeth Fenn, an opening by Niigaanwewidam James Sinclair, and explanations of the book’s influence by leading Canadian historians. -- Publisher's description.
Keywords: Aspect sanitaire; Canada; Canada (Ouest); Canada, Western; Colonisation; Diseases; Diseases. Indians of North America; Government relations. Indians of North America; Government relations. Indians, North American; Health and hygiene; Health and hygiene. Ethnische Beziehungen Gesundheit Indianer Indianerpolitik Kolonisation Sozialer Wandel Indianerpolitik Ethnozid Indianer Krankheit Hunger Sozialer Wandel Indigenous peoples in Canada. Indiens d'Amrique; Health aspects. Ethnic relations. Indians of North America. Indians of North America; Histoire. Canada (Ouest); Histoire. Genre/Form: History. History; Histoire. Indiens d'Amrique; History. Indians of North America; Indians of North America; Maladies; Relations avec l'tat. Canada (Ouest); Relations interethniques; Sant et hygine; history. Colonization; history. Communicable Diseases; history. Health Status. Disease Outbreaks; history. Population Dynamics. Colonialism

They Call Me George: The Untold Story of Black Train Porters and the Birth of Modern Canada - Foster, Cecil (Biblioasis, 2019)
A historical work of non-fiction that chronicles the little-known stories of black railway porters-the so-called "Pullmen" of the Canadian rail lines. The actions and spirit of these men helped define Canada as a nation in surprising ways, effecting race relations, human rights, North American multiculturalism, community building, the shape and structure of unions, and the nature of travel and business across the US and Canada. Drawing on the stories and legends of several of these influential early black Canadians, this book narrates the history of a very visible, but rarely considered, aspect of black life in railway-age Canada. These porters, who fought against the idea of Canada as White Man's Country, open only to immigrants from Europe, fought for and won a Canada that would provide opportunities for all its citizens. -- Publisher's description. Contents: Introduction -- Leaving the station: Stan Grizzle's legacy of social change -- The railways are always hiring: working in white man's country -- "Did you ring, Sir?": Modern luxury and black labour -- The coloured commonwealth: reckoning with ah racist past -- "I know nothing about that": Legislating the colour line -- The ending of empire: Reimagining immigration -- Pressuring parliament: a new kind of Canadian citizenship -- A Creolized country: the black British of the West Indies -- Permanent residence: social identity and the state -- Demerits and deadheading: the rail companies' unreasonable demands -- An uphill battle: Pushing for policy changes -- Fair consideration: The porters gain new ground -- The porters' final fight: A multicultural country -- Beyond the rails: The battle for black identity -- Conclusion: A multicultural brotherhood fulfilling a dream -- Afterword: Appreciating the legacy -- Endnotes -- Index.
Keywords: Black Canadians History; Black people; Black people Canada History; Canada; HISTORY Canada General; History; Noirs canadiens Histoire; Personnes noires Canada Histoire; Porters; Porters Canada History; Porteurs de bagages Canada Histoire; Préposés aux pullmans Canada Histoire; Préposés de service ferroviaire Canada Histoire; Pullman porters; Pullman porters Canada History; Train attendants; Train attendants Canada History

Beginnings to 1866 - Girard, Philip; Phillips, Jim; Brown, R. Blake (A History of Law in Canada, 2019)
This book, the first of 2 volumes, presents the history of law in what is now Canada, from the first European contacts with northern North America in the very early sixteenth century to immediately before Confederation. Divided into four parts, the book first looks at the roots of Canada’s three legal traditions, Indigenous, French and English, in North America, France and England. Part 2 examines the period down to 1701 and the signing of the treaty known as the Great Peace of Montreal in 1701, during which New France was established. Part 3 deals with the eighteenth century – Anglo-French conflict, New France until 1760, the establishment and growth of English colonies of settlement, and, throughout, relations with indigenous peoples and governance of indigenous nations. Part 4 is devoted to the British North American period, after 1815. Indigenous people are central of the narrative throughout, including after 1815 when their influence waned as their land base was largely lost in central and eastern Canada. Included in Part 4 are the Red River settlement and early British Columbia. Although the background to this history are the well-known major political, military, social and economic transformations of this part of North America, the book is principally a legal history set against and integrated with that background. Court systems, the judiciary, the legal professions, are dealt with in every period and for each of the legal traditions, and the areas of law covered include criminal, family, constitutional, commercial, land, succession, and civil and criminal procedure. This volume combines the remarkable flowering of scholarship on Canadian legal history, so much of it fostered and published by the Osgoode Society over 35 years, and much new research. --Publisher's description
Keywords: Canada; Droit Canada Histoire; History; Law; Law Canada History

Direct Action Gets the Goods: A Graphic History of the Strike in Canada - Graphic History Collective; Balmes, Althea; Hill, Gord; Keresztesi, Orion; Lester, David (2019)
Art has always played a significant role in the history of the labour movement. Songs, stories, poems, pamphlets, and comics, have inspired workers to take action against greedy bosses and helped shape ideas of a more equal world. They also help fan the flames of discontent. Radical social change doesn't come without radical art. It would be impossible to think about labour unrest without its iconic songs like "Solidarity Forever" or its cartoons like Ernest Riebe's creation, Mr. Block. In this vein, The Graphic History Collective has created an illustrated chronicle of the strike-the organized withdrawal of labour power-in Canada. For centuries, workers in Canada-Indigenous and non-Indigenous, union and non-union, men and women-have used the strike as a powerful tool, not just for better wages, but also for growing working-class power. This lively comic book will inspire new generations to learn more about labour and working-class history and the power of solidarity. --Publisher's description

1919: A Graphic History of the Winnipeg General Strike - Graphic History Collective; Lester, David (Between the Lines, 2019)
In May and June 1919, more than 30,000 workers walked off the job in Winnipeg, Manitoba. They struck for a variety of reasons-higher wages, collective bargaining rights, and more power for working people. The strikers made national and international headlines, and they inspired workers to mount sympathy strikes in many other Canadian cities. Although the strike lasted for six weeks, it ultimately ended in defeat. The strike was violently crushed by police, in collusion with state officials and Winnipeg's business elites. One hundred years later, the Winnipeg General Strike remains one of the most significant events in Canadian history. This comic book revisits the strike to introduce new generations to its many lessons, including the power of class struggle and solidarity and the brutal tactics that governments and bosses use to crush workers' movements. The Winnipeg General Strike is a stark reminder that the working class and the employing class have nothing in common, and the state is not afraid to bloody its hands to protect the interests of capital. In response, working people must rely on each other and work together to create a new, more just world in the shell of the old. --Publisher's description,     Contents: Preface: Revisiting the workers' revolt by the Graphic history collective -- Acknowledgements -- Introduction: The Winnipeg general strike at 100 by James Naylor -- 1919: A graphic history of the Winnipeg general strike by the Graphic History Collective and David Lester -- The art of labour history: Notes on drawing 1919 by David Lester -- The character of class struggle in Winnipeg: A photo-essay -- Notes -- Bibliography -- Contributors.

Bureaucratic Manoeuvres: The Contested Administration of the Unemployed - Grundy, John (Studies in Comparative Political Economy and Public Policy, 2019)
In Bureaucratic Manoeuvres, John Grundy examines profound transformations in the governance of unemployment in Canada. While policy makers previously approached unemployment as a social and economic problem to be addressed through macroeconomic policies, recent labour market policy reforms have placed much more emphasis on the supposedly deficient employability of the unemployed themselves, a troubling shift that deserves close, critical attention. Tracing a behind-the-scenes history of public employment services in Canada, Bureaucratic Manoeuvres shows just how difficult it has been for administrators and frontline staff to govern unemployment as a problem of individual employability. Drawing on untapped government records, it sheds much-needed light on internal bureaucratic struggles over the direction of labour market policy in Canada and makes a key contribution to Canadian political science, economics, public administration, and sociology.

Cracking Labour's Glass Ceiling: Transforming Lives Through Women's Union Education - Hanson, Cindy; Paavo, Adriane; Sisters in Labour Education (Labour in Canada (Halifax, N.S.), 2019)
Although the health of the trade union movement may rest on its ability to include women in membership and leadership, little attention has been paid to women-only labour education. This original collection contains vibrant example of labour education events and the women involved who develop, implement, research, evaluate and facilitate at them. All the contributors speak from first-hand experience with women-only programs in unions across Canada, the United States and the world. They identify the methods used in pursuit of learner empowerment and transformation, and frankly discuss the outcomes. These real-life examples offer practical guidance and inspiration for all who create and support activist learning within unions and other social-justice organizations. -- Publisher's description

Reading Canadian Women's and Gender History - Janoviček, Nancy; Nielson, Carmen J. (Studies in gender and history, 2019)
Although Canadian womens history is now nearly forty years old, no volume exists that reflects explicitly upon the fields evolution and assesses its historiographical context. This retrospective is not merely summative; the essays in this collection are analytical engagements with the current state of the field, which draw on its rich past to generate new knowledge and propose innovative avenues for inquiry. The dual purposes of this collection are to contemplate the fields past and to contribute productively to its future. These thirteen original essays are written by scholars at all career stages. The diversity of these authors perspectives illustrates the contributions that Canadian scholarship has had in international dialogues about womens and gender history and that it continues to be a vibrant area of research. The collection includes chapters about the principal sub-fields in Canadian womens and gender history, including specialized chapters on Québecois, Indigenous, Black, and immigrant womens histories, religious history, labour history, war and society, history of sexuality, the history of reproductive labour and reproductive justice, two essays on the history of feminism that, taken together, cover the period from 1850 to the present, and a thematic essay on the colonial period. --Publisher's description
Keywords: Canada; Feminism; Feminism Canada History; Feminismus; Femmes Canada Conditions sociales; Femmes Canada Histoire; Femmes Conditions sociales Canada Histoire; Frau; Féminisme Canada Histoire; History; Identité sexuelle Canada Histoire; Kanada; Women; Women Canada History; Women Canada Social conditions; Women Social conditions; Women's studies; Women's studies Canada History; Études sur les femmes Canada Histoire

Unearthing Justice: How to Protect Your Community from the Mining Industry - Kuyek, Joan (Between the Lines, 2019)
The mining industry continues to be at the forefront of colonial dispossession around the world. It controls information about its intrinsic costs and benefits, propagates myths about its contribution to the economy, shapes government policy and regulation, and deals ruthlessly with its opponents. Brimming with case studies, anecdotes, resources, and illustrations, Unearthing Justice exposes the mining process and its externalized impacts on the environment, Indigenous Peoples, communities, workers, and governments. But, most importantly, the book shows how people are fighting back. Whether it is to stop a mine before it starts, to get an abandoned mine cleaned up, to change laws and policy, or to mount a campaign to influence investors, Unearthing Justice is an essential handbook for anyone trying to protect the places and people they love. --Publisher's description
Keywords: Canada; Citizen participation; Environmental policy; Environmental protection; Indigenous peoples; Mineral industries; Mines and mineral resources; Native peoples; Politics and government

Slagflower: Poems Unearthed from a Mining Town - Leduc, Thomas (Latitude 46, 2019)
Debut collection of poetry from Thomas Leduc, City of Greater Sudbury's past Poet Laureate and the fourth generation of a mining family. Stagflower captures a city struggling to grow beyond its past and become more than just a mining town, while reflecting the internal human conflict to be more than family history, more than a past. --Publisher's description. "At one time, this city / had a single plan / for every young man; / a straight, well-worn path / from their front doors / to an open rock face / at the end of a mine shaft. / A path chiselled out of stone, / a path paved in nickel. / Every young man / wanted his millwright ticket, / studied the ticking of gears, / the composition of rock; / had the culture of mining / drilled into him. / Plans were passed down / from lunch pail / to lunch pail. / Fathers and sons dug the same holes / fought the same fights. / How many boys / has this rock hardened / into men." -- Chiselled Out of Stone, poem by Thomas Leduc. Table of contents: Birthmark -- Rite of passage -- Buffalo souls -- The taste of sulfur -- Slagflower.

Magnificent Fight: The 1919 Winnipeg General Strike - Lewycky, Dennis (Fernwood, 2019)
In May 1919, 30,000 Winnipeg workers walked away from their jobs, shutting down large factories, forcing businesses to close and bringing major industries to a halt. Mounted police and hired security, at the behest of the ruling class, violently ended the protest after six weeks. Two men were killed. What started as trade union revolt, the Winnipeg General Strike became a mass protest and was branded as a revolution. In Magnificent Fight, Dennis Lewycky lays out the history of this iconic event, which remains the biggest and longest strike in Canadian history. He analyzes the social, political and economic conditions leading up to the strike. He also illustrates the effects the strike had on workers, unions and all three levels of government in the following decades. Far from a simple retelling of the General Strike, Magnificent Fight speaks to the power of workers' solidarity and social organization. And Lewycky reveals the length the capitalist class and the state went to in protecting the status quo. By retelling the story of the Strike through the eyes of those who witnessed it, Lewycky's account is both educational and entertaining. --Publisher's description

Enforcing Exclusion: Precarious Migrants and the Law in Canada - Marsden, Sarah Grace (Law and society series (Vancouver, B.C.), 2019)
In Canada’s liberal dream, the law extends its benefits to everyone. But the law also determines who is included in that “everyone.” Migrant workers, long welcomed in Canada for their labour, are often excluded from both workplace protections and basic social benefits such as health care, income assistance, and education due to their lack of permanent status. Enforcing Exclusion recasts what migration status means to both the state and to non-citizens. Through interviews with migrants and their advocates, Sarah Marsden shows that migrants face enforcement through law, policy, and practice, affecting their ability to address adverse working conditions and their interactions with institutions such as hospitals, schools, and employment standards boards. Canadian immigration laws create a status hierarchy; those at the bottom experience markedly different access to the protections and benefits of law. This book documents the impact of Canada’s system of migration enforcement on people’s lives and questions the adequacy of human-rights-based responses in addressing its exclusionary effects. -- Publisher's description. Contents: Introduction -- The Creation and Growth of Precarious Migration in Canada: “Illegal” Migration and the Liberal State -- Status, Deportability, and Illegality in Daily Life -- Working Conditions and Barriers to Substantive Remedies -- Exclusion from the Social State: Health, Education, and Income Security -- Multi-Sited Enforcement: Maintaining Subordinate Membership -- Rights and Membership: Toward Inclusion? -- Postscript -- Appendix A: Migrant Participant Profiles -- Appendix B: Sample Interview Script.

Papergirl - McCracken, Melinda; Jackson, Penelope (Roseway Publishing, an imprint of Fernwood Publishing, 2019)
Ten-year-old Cassie lives with her working-class family in 1919 Winnipeg. The Great War and Spanish Influenza have taken their toll, and workers in the city are frustrated with low wages and long hours. When they orchestrate a general strike, Cassie--bright, determined and very bored at school--desperately wants to help. She begins volunteering for the strike committee as a papergirl, distributing the strike bulletin at Portage and Main, and from her corner, she sees the strike take shape. Threatened and taunted by upper-class kids, and getting hungrier by the day, Cassie soon realizes that the strike isn't just a lark--it's a risky and brave movement. With her impoverished best friend, Mary, volunteering in the nearby Labour Café, and Cassie's police officer brother in the strike committee's inner circle, Cassie becomes increasingly furious about the conditions that led workers to strike. When an enormous but peaceful demonstration turns into a violent assault on Bloody Saturday, Cassie is changed forever. Lively and engaging, this novel is a celebration of solidarity, justice and one brave papergirl. -- Publisher's description
Keywords: 1919; Children's stories; Fiction; General Strike, Winnipeg, Man., 1919 Juvenile fiction; Grève générale, Winnipeg, Man., 1919 Romans, nouvelles, etc. pour la jeunesse; Historical fiction; Juvenile works; Manitoba Winnipeg; Papergirls; Papergirls Manitoba Winnipeg Juvenile fiction

Dix concepts pour penser le nouveau monde du travail - Mercure, Daniel; Vultur, Mircea (Collection Sociologie contemporaine, 2019)
Au cours des dernières décennies, de nombreux changements économiques, politiques et culturels ont bouleversé la nature du travail, la manière de l’organiser ainsi que la relation d’emploi. Ces transformations nécessitent de revoir, de critiquer et d’actualiser les principaux concepts à partir desquels la sociologie analyse le monde du travail. Dans cet ouvrage, les concepts revisités sont les suivants : salariat, précarité, informalité, conflit, contrôle et organisation du travail, qualification et compétence, rapport au travail, parcours professionnel, insertion professionnelle, temporalités. Chacun des concepts retenus est analysé selon une perspective critique, qui consiste à remettre en question les assises théoriques et empiriques de ceux-ci, et une perspective analytique, qui vise à arrimer ces concepts fondamentaux aux nouvelles réalités du monde du travail. --Publisher's description
Keywords: COMPETENCE; CONFLIT; CONTROLE; INFORMALITE; Industrial sociology; Methods engineering; ORGANISATION; Organisation du travail; PRECARITE; PROFESSIONNELLE; SALARIAT; Sociologie du travail; Sociologie industrielle; TRAVAIL; Work Simplification; Work environment

Walmart: Diary of an Associate - Meunier, Hugo (Fernwood, 2019)
In 2012, journalist Hugo Meunier went undercover as a Walmart employee for three months in St. Leonard, Quebec, just north of Montreal. In great detail, Meunier charts the daily life of an impoverished Walmart worker, referring to his shifts at the box store giant as “somewhere between the army and Walt Disney.” Each shift began with a daily chant before bowing to customer demands and the constant pressure to sell. Meanwhile Meunier and his fellow workers could not afford to shop anywhere else but Walmart, further indenturing them to the multi-billion-dollar corporation. Beyond his time on the shop floor, Meunier documents the extraordinary efforts that Walmart exerts to block unionization campaigns, including their 2005 decision to close their outlet in Jonquiere, QC, where the United Food and Commercial Workers union had successfully gained certification rights. A decade later he charts the Supreme Court of Canada ruling that exposed the dubious legal ground on which Walmart stood in invoking closure and throwing workers out on the street. In Walmart: Diary of an Associate, Meunier reveals the truths behind Walmart’s low prices. It will make you think twice before shopping there. --Publisher's description

Working Women in Canada: An Intersectional Approach - Nichols, Leslie; Forrest, Anne; Lippel, Katherine; Premji, Stephanie; Tyyskä, Vappu; Aggarwal, Pramila; Ignagni, Esther; Prentice, Susan; Acker, Sandra; Muzzin, Linda; Knight, Melanie; Gabay, Danielle; et al. (Canadian Scholars/Women's Press, 2019)
In this edited collection, Leslie Nichols weaves together the contributions of accomplished and diverse scholars to offer an expansive and critical analysis of women’s work in Canada. Students will use an intersectional approach to explore issues of gender, class, race, immigrant status, disability, sexual orientation, Indigeneity, age, and ethnicity in relation to employment. Drawing from case studies and extensive research, the text’s eighteen chapters consider Canadian industries across a broad spectrum, including political, academic, sport, sex trade, retail, and entrepreneurial work. Working Women in Canada is a relevant and in-depth look into the past, present, and future of women’s responsibilities and professions in Canada. Undergraduate and graduate students in gender studies, labour studies, and sociology courses will benefit from this thorough and intersectional approach to the study of women’s labour. Features include tables, case studies, a glossary of key terms, and chapter introductions and conclusions to assist with student comprehension encourages further learning by concluding each chapter with discussion questions, a list of additional key readings, and an extensive reference list provides a broad portrait of women’s work in Canada with contributions from over 20 scholars. --Publisher's description

Confronting Canadian Migration History - Ross, Daniel (Active History, 2019)
Confronting Canadian Migration History means two things. First, engaging with the history of population movements into, through, and from this territory, and their importance for our history as a multiethnic settler society. This has been one of the central projects of migration historians in Canada in recent decades. Second, to make and maintain a place for that historical knowledge in contemporary discussions of migration, and in doing so confront the present with the past. That latter goal is at the heart of this collection, which assembles in one volume fifteen texts published on ActiveHistory.ca over the last four years. --Publisher's description, Contents: Introduction / Daniel Ross. [Part] 1. Refugee migrations. Canada’s complicated history of refugee reception / Stephanie Bangarth -- Using old photographs to gain new perspectives on refugees, past and present / Sonya de Laat -- When to speak, when to act: Reflections on the recent MS St. Louis apology / Andrea Eidinger and Laura Madokoro -- Remembering the Prague Spring refugees / Jan Raska -- Little Bear’s Cree and Canada’s uncomfortable history of refugee creation / Benjamin Hoy. [Part] 2. Migration experiences and representations. Creating the Canadian mosaic / Ryan McKenney and Benjamin Bryce -- Conversations with Egyptian Uber drivers: Why emigrate? Why Canada? / Michael Akladios -- Old stock Canadians: Arab settlers in Western Canada / Sarah Carter -- Not so accidental: Farmworkers, car crashes, and capitalist agriculture / Edward Dunsworth -- Arab-Canadian foodscapes and authenticity / Michael Akladios. [Part] 3. Nativism and exclusion White Supremacy, political violence, and community, 1907 and 2017 / Laura Ishiguro and Laura Madokoro -- Immigration and White Supremacy: Past and present / David Atkinson -- Pork cuts: The sharp edges of nativism in Southern Europe / Aitana Guia -- X-Rays and the discriminatory science of migration / Laura Madokoro -- Baba wore a burqa, and Nona wore a niqab / Franca Iacovetta and Karen Dubinsky.

A Grander Vision: My Life in the Labour Movement - Ryan, Sid (Dundurn, 2019)
A stirring, heartfelt manifesto written by a man who fervently believes in what workers with their civil society allies can achieve for the good of all. Sid Ryan, one of Canada's most courageous and progressive union leaders, draws on the experience of his varied and colourful life to show what is right with the labour movement, what is wrong, and what has to change if it is to avoid becoming irrelevant. He calls for the adoption of Social Movement Unionism, in which labour forges an alliance with other progressive elements in civil society, taking up the cause of young people, precarious workers, and immigrants. He demands a renewed commitment to the NDP, the party that was built by unions, and he argues that the Leap Manifesto should become the pillars of the movement in Canada. --Publisher's description. Contents: Foreword by Gerry Adams -- Growing up in Ireland -- A new life in Canada -- President of CUPE Ontario -- Bob Rae and the social contract -- At home in the world -- OFL president -- The grander vision.
Keywords: Canada. Human rights movements. Labor movement. Progressivism (Canadian politics) Social conditions; Canada. Progressivism (Canadian politics) Human rights movements; Labor movement

Masters and Servants: The Hudson's Bay Company and Its North American Workforce, 1668-1786 - Stephen, Scott P. (University of Alberta Press, 2019)
With Masters and Servants, Scott P. Stephen has revealed startling truths about the men of the Hudson's Bay Company. Rather than dedicating themselves body and soul to the Company's interests, these workers hired out like domestic servants, joining a 'household' with its attendant norms of duty and loyalty. Through painstaking documentary research, Stephen shines welcome light on the lives of these largely overlooked historical actors. The household system produced a remarkably stable political-economic entity, connecting early Canadian resource extraction to larger trends in British imperialism and its emerging social relations. An essential book for labour historians, Masters and Servants will appeal to scholars of early modern Britain, the North American fur trade, Western social history, or business history, and anyone intrigued by the reach of the HBC. -- Publisher's description
Keywords: Canada; Compagnie de la Baie d'Hudson Histoire; Compagnie de la Baie d'Hudson Personnel Histoire; Contract labor; Contract labor Canada History; Employees; Employés de maison Canada Histoire; Employés de maison Grande-Bretagne Histoire; Fourrures Commerce Canada Histoire; Fur trade; Fur trade Canada History; Great Britain; History; Household employees; Household employees Canada History; Household employees Great Britain History; Hudson's Bay Company; Hudson's Bay Company Employees History; Hudson's Bay Company Histoire; Hudson's Bay Company History; Hudson's Bay Company Personnel; Main-d'oeuvre contractuelle Canada 1500-1800; Main-d'œuvre contractuelle Canada Histoire; Serviteurs Canada 1500-1800

Change and Continuity: Canadian Political Economy in the New Millennium - Thomas, Mark P; Vosko, Leah F.; Lyubchenko, Olena; Fanelli, Carlo (Carleton library series, 2019)
In a period characterized by growing social inequality, precarious work, the legacies of settler colonialism, and the emergence of new social movements, Change and Continuity presents innovative interdisciplinary research as a guide to understanding Canada's political economy and a contribution to progressive social change. Assessing the legacy of the Canadian political economy tradition — a broad body of social science research on power, inequality, and change in society — the essays in this volume offer insight into contemporary issues and chart new directions for future study. Chapters from both emerging and established scholars expand the boundaries of Canadian political economy research, seeking new understandings of the forces that shape society, the ensuing conflicts and contradictions, and the potential for social justice. Engaging with interconnected topics that include shifts in immigration policy, labour market restructuring, settler colonialism, the experiences of people with disabilities, and the revitalization of workers' movements, this collection builds upon and deepens critical analysis of Canadian society and considers its application to contexts beyond Canada. --Publisher's description.

The Voice of Labour: A Life in Toronto's Construction Industry - Toppan, Marino; Principe, Angelo; Breda, Paola; Frank Iacobucci Centre for Italian Canadian Studies (Frank Iacobucci Centre for Italian Canadian Studies monograph series., 2019)
The memoirs of union organizer Marino Toppan, during the union organizing days of the residential construction "jungle" in Toronto: 1955-1980.

The Class Politics of Law: Essays Inspired by Harry Glasbeek - Tucker, Eric; Fudge, Judy (Fernwood Publishing, 2019)
For nearly fifty years, Professor Harry Glasbeek has been at the forefront of legal scholars and public intellectuals challenging assumptions and understandings about the injustices embedded in the economic, social, political and legal orders of Western capitalist democracies. His writings and teachings have influenced generations of law students, academics and activists. [This book] brings together eleven incisive contributions from pre-eminent scholars across several disciplines activated by the same desire for democracy and justice that Glasbeek advances, showing how capitalism shapes the law and how the law protects capitalism. This collection foregrounds a class analysis of the laws responses to corporate killing, workplace violence, surveillance, worker resistance and income inequality, among other issues. --Publisher's description
Keywords: Economic aspects. Law; Political aspects. Law; Political aspects. Sociological jurisprudence; Sociological jurisprudence. Law

The Labour Companion: A Bibliography of Printed Sources of Canadian Labour History - Vaisey, G. Douglas (Canadian Committee on Labour History, 2019)
The Canadian Labour Bibliography was an initiative of the Committee on Canadian Labour History in the 1970s. The initial efforts to create an annual reading list of publications dealing with Canadian labour topics led to the creation of The Labour Companion: a bibliography of Canadian labour history based on materials printed from 1950 to 1975. ...The enthusiasm that greeted The Labour Companion prompted Greg Kealey, then teaching at Dalhousie University, to obtain a Social Sciences and Humanities Research Council grant for a much larger product – a comprehensive reading list of books, pamphlets, articles and theses pertinent to the Canadian labour experience (the labour movement, trade unions, living conditions, key legislation, etc.). The intent was to build on the 1980 bibliography and to catalogue the published record on the Canadian working class from earliest times to 1985. Items of more recent vintage have crept in, but no effort was made to deal comprehensively with the entire published record from the late 1980’s forward. To locate that material, researchers should consult Michael Lonardo’s Canadian Labour History Bibliography, an electronic compilation covering 1976 to 2009, found at Memorial University Library https://www.library.mun.ca/qeii/labour/ --Introduction

Disrupting Deportability: Transnational Workers Organize - Vosko, Leah F. (ILR Press, an imprint of Cornell University Press, 2019)
In an original and striking study of migration management in operation, Disrupting Deportability highlights obstacles confronting temporary migrant workers in Canada seeking to exercise their labor rights. Leah F. Vosko explores the effects of deportability on Mexican nationals participating in Canada's Seasonal Agricultural Worker Program (SAWP). Vosko follows the decade-long legal and political struggle of a group of Mexican SAWP migrants in British Columbia to establish and maintain meaningful collective representation. Her case study reveals how modalities of deportability—such as termination without cause, blacklisting, and attrition—destabilize legally authorized temporary migrant agricultural workers. Through this detailed exposé, Disrupting Deportability concludes that despite the formal commitments to human, social, and civil rights to which migration management ostensibly aspires, the design and administration of this "model" temporary migrant work program produces conditions of deportability, making the threat possibility of removal ever-present. --Publisher's description
Keywords: Agricultural laborers, Foreign; Agricultural laborers, Foreign British Columbia; British Columbia; CANADA; Canada; Deportation; Deportation British Columbia; Foreign workers Labor unions Organizing; Foreign workers Labor unions Organizing British Columbia; Foreign workers, Mexican Civil rights Canada; POLITICAL SCIENCE Labor & Industrial Relations; Precarious employment; Precarious employment British Columbia; Travail précaire Colombie-Britannique; Travailleurs agricoles étrangers Colombie-Britannique; Travailleurs étrangers Syndicalisation Colombie-Britannique; Travailleurs étrangers mexicains Droits Canada

The Great Canadian Sedition Trials: The Courts and the Winnipeg General Strike, 1919-1920 - Walker, Jack (University of Manitoba, Faculty of Law, 2019)
Few occurrences in modern times have produced the social upheaval, fear, and hatred that were seen during the Red Scare of 1919. Few events have brought forth such a frenzy of mob action and intolerance, or can match the excitement and drama. One of life's coincidences led me to study one of the manifestations of the Red Scare: the trials that grew out of the Winnipeg General Strike of 1919. Their prominent place in Manitoba's legal history has made them deserving of the title "The Great Canadian Sedition Trials." --From author's prologue

With Glowing Hearts: How Ordinary Women Worked Together to Change the World (and Did) - Webber, Jennifer Wynne (Scirocco Drama, 2019)
When the "Kirkland Lake gals of 1941" begin to share their story with a present-day audience, a siren sounds and they soon find themselves pulled right back into the fateful winter of 1941-42. There, they gather again at the mine-head, waiting for word on the men trapped underground, as their fear and rage builds. When the husband of one of the women is badly injured, their desire to help her quickly leads them into a much larger campaign to help all the families they can. Before long, they've become the heart and soul of a large-scale union-organizing drive that is fuelled by their sheer will - and sometimes giddy enthusiasm - but that is also put to the test by their own inexperience, a bitter strike, and the brutal force of the powers-that-be. --Publisher's description
Keywords: Drama. Labor unions; Drama. Labor unions. Miners. Women labor union members; Drama. Miners; Drama. Women labor union members; Gold Miners' Strike, Kirkland Lake, Ont., 1941-1942; Kirkland Lake; Ontario

A New Kind of Union: Unifor and the Birth of the Modern Canadian Union - Wilson, Fred (Lorimer, 2019)
The inside story of how two important Canadian unions decided to create a new kind of union with new ways of fighting for worker's rights In the fall of 2011 the leaders of two of the biggest Canadian unions, Canadian Auto Workers union (CAW) President Ken Lewenza and Communications, Energy and Paperworkers Union of Canada (CEP) President Dave Coles, found common ground. The labour movement was in crisis. They faced hostile governments, union busting corporations, and declining membership. Something drastic needed to be done. Fred Wilson was an insider in the process by which the leaders of these two large organizations found a way to create a new kind of union, one that was more democratic, more inclusive, and more powerful. Two years later, a new union with a new name was founded. From its inception, Unifor has been a source of optimism and inspiration that a fairer, more secure future can be won for working people, and that unions can adapt to changing times and remain a relevant voice for workplace and social justice. This book describes how this came about. --Publisher's description
Keywords: CAW-Canada; CAW-Canada Histoire; CAW-Canada History; Canada; Communications, Energy and Paperworkers Union of Canada; Communications, Energy and Paperworkers Union of Canada History; History; Labor unions; Labor unions Canada History; Labor unions Mergers; Labor unions Mergers Canada History; Syndicat canadien des communications, de l'énergie et du papier Histoire; Syndicats Canada Histoire; Syndicats Fusion Canada Histoire; Unifor (Labor union) History; Unifor (Syndicat) Histoire